UPAYA PEMBATALAN PUTUSAN ARBITRASE DI INDONESIA BERDASARKAN PERSPEKTIF HUKUM ARBITRASE INTERNASIONAL - Made Cinthya Puspita Shara (Fakultas Hukum Universitas Dwijendra, 2023)
Dispute resolution is generally known to be resolved through litigation and non-litigation processes. Non-litigation legal efforts or alternative dispute resolution are agreements that are often chosen by business actors in the world of trade in goods and services. The purpose of this study is to find out more about arbitration regulations in both national and international law, especially in efforts to cancel arbitration decisions. This study uses a normative legal research method. requests for cancellation of decisions have also been regulated in the International Center for Settlement of Investment Disputes Rule can only be made in writing and not verbally. The results of the study indicate that the formation of an arbitration panel is considered inappropriate where if the formation is carried out through unreasonable stages as stated in the clause of the agreement of the parties, but the parties do not file objections and do not file a request for cancellation of the arbitration decision only because of the reason for the formation of the board or panel of arbitrators that is not appropriate then. The conclusion is that the arbitration decision will still be declared valid and final and binding. Meanwhile, in the case of a request for cancellation of an arbitration decision, it is not recognized in The United Nations Commission on International Trade Law Rule. In the event that the parties have different understandings during the resolution of the case, this can be used as a basis for submitting a request for interpretation.